Optical properties, electronic structures, and photocatalytic performances of bandgap-tailored Srbi2Nb2−xVxO9 compounds - Hwang, Sung Won; Noh, Tae Hoon; Cho, In Sun (Catalysts, 2019)
Layered perovskite compounds of SrBi2Nb2−xVxO9 (x = 0.0, 0.02, 0.04, 0.06, and 0.08) were synthesized via a solid-state reaction method. Their optical properties, electronic band structures, and photocatalytic activities under visible light irradiation were investigated for the first time. The incorporation of vanadium into the SrBi2Nb2O9 lattice reduced the bandgap energies, allowing the compounds to effectively absorb visible light. Electronic band structure calculations revealed that the V 3d orbitals caused bandgap narrowing by forming an additional band below the conduction band, while the O 2p and Bi 6p orbitals dominantly contributed to the formation of the valence band. The photocatalytic activity tested under visible light irradiation (>420 nm) revealed that it increased linearly with the V content in the SrBi2Nb2−xVxO9 compounds until saturation at x = 0.06, which was attributed to improved visible light absorption originating from the reduced bandgap energies.
Keywords: Band structure; Optical properties; Photocatalysis; SrBi2Nb2O9; Vanadium incorporation; Visible-light-active